Expecting Refugees in Latvia: Negative Stereotyping - Murašovs Vadims; Ruža Aleksejs; Raščevskis Vitālijs; Dombrovskis Valērijs (Economics and Business)
In response to a dramatic increase of illegal immigration in the European Union, in the fall of 2015 Latvia agreed to accept several hundreds of refugees on its soil. Nevertheless, Latvian society remains very sceptic about these plans, and reportedly demonstrates strong negative attitudes towards refugees. According to the survey, by the end of 2015 the factual experience of interaction with refugees did not exceed ten per cent of Latvian population. This suggests that most of the real attitudes are formed by mass media and other socialisation agents. In order to uncover the nature of these feelings, the present study has been designed to make an in-depth social psychological study on attitudes. One thousand Latvian residents evenly representing Latvia’s demography have taken part in this study. A modified Stephan’s Prejudicial Attitude Survey has been used to study prejudice. Negative stereotyping represents one of the emotional components of attitudes towards refugees. The results illustrate the palette of emotions and the level of their expression in Latvian society, and highlight the feelings, which may shape the identity of the in-group.